Common Problems and Countermeasures of Doctor-Patient Communication Record. (March 2014) - Han, Yichao; Peng, Ye; Yang, Xiufang; Xie, Na
Abstract Objective. To regulate the doctor-patient communication record, reduce defects and errors in doctor-patient communication and reduce the occurrence of medical disputes, so as to guarantee the quality of medical treatment. Method. Randomly selecting 585 terminal medical records of January 2013 in our hospital, performing quality control checks on the doctor-patient communication records in the medical records, recording the effects of quality control in Excel and performing statistical analysis. Results. Of the 585 medical records, 180 medical records have defects in the doctor-patient communication record, the defect rate is 30.77%, there are a total of 199 defects altogether, the commonly occurring defects are as follows: incomplete general information of a patient (10.94%); incomplete or simple communication content (6.15%), absence of corresponding doctor-patient communication record such as the absence of the automatic discharge conversation record or informed consent for blood transfusion and blood product (5.98%), and communication record signed by an unauthorized person (3.07%). Conclusion. Strengthening the sense of responsibility of doctors, strengthening the effective doctor-patient communication and regulating the doctor-patient communication record can effectively prevent the occurrence of medical disputes.